Construction of a Transformation Vector Containing Cucumber Mosaic Virus (CMV) Coat Protein (CP) Gene and Development of an Agrobacteriumtransformation Procedure for Chilli - Lim, Jee Hian (2003)
Chilli (Capsicum annuum L.) is one of the major vegetable and spice crops grown widely, yet it suffers great losses due to infection by various viruses, including Cucumber Mosaic Virus (CMV). The conventional breeding of chilli hybrids for improved disease resistance is a long process with problems of interspecific incompatibility. The objectives of the study were to construct a transforming vector containing Cucumber Mosaic Virus (CMV) Coat Protein (CP) and development of an Agrobacterium-transformation procedure which can offer solutions to these problems. This study was approached primarily from the molecular aspect which the construct of a CMV CP has been successfully cloned. The cloned fragments were 655 bp and exhibited more than 90% similarity to those published CMV CP gene sequences. SDS-PAGE analysis showed the size of the expressed coat protein to be similar to the predicted size of 30 kD based on the DNA sequences. Western blot analysis was also conducted to confirm the bacterial expressed coat proteins. All these verified that the cloned genes were translatable CMV CP genes.